2013
DOI: 10.1017/s1431927613012294
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of {113} Defect Formation in Silicon: Clustering of Interstitial–Vacancy Pairs Studied by In Situ High-Resolution Electron Microscope Irradiation

Abstract: Abstract:We report the direct visualization of point defect clustering in $113% planes of silicon crystal using a transmission electron microscope, which was supported by structural modeling and high-resolution electron microscope image simulations. In the initial stage an accumulation of nonbonded interstitial-vacancy~I-V! pairs stacked at a distance of 7.68 Å along neighboring atomic chains located on the $113% plane takes place. Further broadening of the $113% defect across its plane is due to the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Numerous HRTEM investigations have been carried out to identify their complex structure. It was demonstrated that the formation of {113} defects is based on the aggregation of interstitials and vacancies during annealing of implanted zones at around 650°C-850 °C [25,26]. However, this is the first observation of these specific defects in Si after plastic deformation and it will be the object of further investigations to understand the mechanisms of formation in the present conditions.…”
Section: Effect Of Temperaturementioning
confidence: 79%
“…Numerous HRTEM investigations have been carried out to identify their complex structure. It was demonstrated that the formation of {113} defects is based on the aggregation of interstitials and vacancies during annealing of implanted zones at around 650°C-850 °C [25,26]. However, this is the first observation of these specific defects in Si after plastic deformation and it will be the object of further investigations to understand the mechanisms of formation in the present conditions.…”
Section: Effect Of Temperaturementioning
confidence: 79%
“…Point defects dominant in thermal equilibrium at temperatures are thought to be vacancies rather than self-interstitials. Recently, Fedina et al reported clustering of vacancy and interstitial pairs for so-called {113}-defect formations during in situ HREM irradiation [62]. They found planar fourfold-coordinated defects in the process, though it remains unclear whether such kinds of point-like defects are detectable using that method.…”
Section: Dislocation Motion Related To Point Defect Accumulation and ...mentioning
confidence: 99%